Analysis of User Experience and Redesign of the User Interface in the Unsrat Informatics Engineering E-Journal using the Five Planes Method and Usability Scale - Nur'ain Burhan; Virginia Tulenan; Sary D. E. Paturusi (Jurnal Teknik Informatika, 2025)
Abstract — In the rapidly evolving era of information technology, e-journals have become the primary means for researchers and academics to access and disseminate scientific knowledge. However, the importance of user interface (UI) in ejournal platforms is often overlooked, despite its significant impact on user experience (UX) and overall application value. Therefore, this research aims to conduct an in-depth analysis of the UI and UX of the Jurnal Teknik Informatika Universitas Sam Ratulangi website. Utilizing the Five Planes method, we identify weaknesses in the UI design and provide recommendations for improvement tailored to user needs. We also employ the System Usability Scale (SUS) to measure user satisfaction with the implemented changes. The research findings show a significant increase in user satisfaction from the initial design to the recommended design, with usability scores rising from 61.1 to 77.225. Our recommendations can be utilized by the managers of Jurnal Teknik Informatika to enhance user interaction with the website and effectively disseminate knowledge in the field of informatics. Suggestions for further research include conducting periodic evaluations and employing diverse usability testing methods to gain a more comprehensive understanding of user experience.Key words — E-Journal; User Interface; User Experience; Five Planes; System Usability Scale.Abstrak — Dalam era teknologi informasi yang berkembang pesat, E-journal telah menjadi sarana utama bagi peneliti dan akademisi untuk mendapatkan akses dan mendistribusikan pengetahuan ilmiah. Namun, pentingnya antarmuka pengguna dalam platform E-journal seringkali terabaikan, padahal memiliki dampak besar terhadap pengalaman pengguna dan nilai aplikasi secara keseluruhan. Oleh karena itu, penelitian ini bertujuan untuk melakukan analisis mendalam terhadap UI dan UX dari website Jurnal Teknik Informatika Universitas Sam Ratulangi. Dengan menggunakan metode Five Planes, penelitian ini mengidentifikasi kelemahan dalam desain UI dan memberikan rekomendasi perbaikan yang sesuai dengan kebutuhan pengguna. Penelitian ini juga menggunakan System Usability Scale (SUS) untuk mengukur kepuasan pengguna terhadap perubahan yang diimplementasikan. Hasil penelitian menunjukkan peningkatan signifikan dalam kepuasan pengguna dari desain awal hingga desain rekomendasi, dengan nilai usability meningkat dari 61,1 menjadi 77,225. Rekomendasi penelitian ini dapat digunakan oleh pengelola Jurnal Teknik Informatika untuk meningkatkan interaksi pengguna dengan website dan menyebarkan pengetahuan di bidang teknik informatika secara lebih efektif. Saran untuk penelitian selanjutnya termasuk melakukan evaluasi berkala dan menggunakan metode pengujian usability yang beragam untuk mendapatkan pemahaman yang lebih holistik tentang pengalaman pengguna.Kata kunci — E-Journal; User Interface; User Experience; Five Planes; System Usability Scale.